Anthropogenic chemicals and their impacts on microbes living in buildings. Issue 3 (10th October 2020) - Hu, Jinglin; Hartmann, Erica M.
Summary: Humans spend the vast majority of their time indoors where complex interactions occur among indoor anthropogenic chemicals, indoor microbiomes and human occupants. This paper summarizes previous work addressing interactions between anthropogenic chemicals associated with indoor household products and building materials, and microorganisms found within the built environment. Water availability seems to determine the extent to which microbes are impacted by anthropogenic chemicals, since desiccation remains one of the primary stressors regulating microbial viability indoors. Several lines of evidence suggest that both fungi and bacteria are capable of transforming biodegradable ingredients originating from various products used indoors when water is present. Previous research also establishes positive and significant correlations between anthropogenic chemicals that are antimicrobial and antibiotic resistance gene abundance. As researchers move towards understanding complex indoor environments as well as the role of anthropogenic chemicals in shaping microbiomes, in situ activities associated with the viable indoor microbial population merit more attention. Abstract : Humans spend the vast majority of their time indoors where complex interactions occur among indoor anthropogenic chemicals, indoor microbiomes, and human occupants. This paper summarizes previous work addressing interactions between anthropogenic chemicals associated with indoor household products and building materials, and microorganisms found within the built environment. As researchers move towards understanding complex indoor environments as well as the role of anthropogenic chemicals in shaping microbiomes, in situ activities associated with the viable indoor microbial population merit more attention.